2021
DOI: 10.1109/access.2021.3049768
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Feasibility of Game-Theory-Based Demand Response Management by Practical Implementation

Abstract: Demand response (DR) has been widely recognized as an effective solution to help mitigate the stresses imposed on power grids. As new concepts evolve, DR induces various interactions among multiple emerging entities, which further complicates the decision-making processes in grid operations. Recently, game theory (GT) has received great attention in DR management, due to its ability to handle complex decision-making problems. Numerous theoretical GT-based approaches have been proposed for addressing various DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In the SG approach for small-and middle-sized users, the master-slave relation among game players is largely clear. That is, energy supply side (i.e., energy retailer [89], utility company [90], and power grid [91]) or energy management side (i.e., energy management center [92] and load aggregator [93]) participates in the game as leader, while the energy demand side (i.e., household appliances and EVs) is in the follower position. For the follower, the optimization problem generally aims to minimize/maximize energy cost/utility, whereas for the leader, the optimization goals have diversified forms, which can be divided into profit-oriented and social welfare-oriented forms.…”
Section: ) Stackelberg Gamementioning
confidence: 99%
“…In the SG approach for small-and middle-sized users, the master-slave relation among game players is largely clear. That is, energy supply side (i.e., energy retailer [89], utility company [90], and power grid [91]) or energy management side (i.e., energy management center [92] and load aggregator [93]) participates in the game as leader, while the energy demand side (i.e., household appliances and EVs) is in the follower position. For the follower, the optimization problem generally aims to minimize/maximize energy cost/utility, whereas for the leader, the optimization goals have diversified forms, which can be divided into profit-oriented and social welfare-oriented forms.…”
Section: ) Stackelberg Gamementioning
confidence: 99%
“…Two utility functions are modeled to meet the power supply and demand objectives. According to [37], DR is a challenging decision-making process since multiple entities must interact. Therefore, the game theory method is appealing due to its capacity to handle complicated decision-making issues.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…In [31]- [36], the DR concept in the electricity market is formulated to increase the adoption to reality of MGs' operating conditions. In [37], the DR method is joined to a real-time pricing strategy under general conditions.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…To test the balanced coordination between the community-integrated energy system and electric vehicle charging stations and the effective role of flexible demand response and RES, a real-time case study in North China has been considered. Stackelberg game-based DR models have been a great source of benefits for providing power system stability to both consumers and the main grid [24]- [26]. From [8]- [13] to [27]- [29], it has been observed that the research interest was on the robust solution and lack of focus on the opportunistic solution.…”
mentioning
confidence: 99%